SEMIOTIKA WARNA HIJAU DALAM AL-QURAN (ANALISIS SEMIOTIKA ROLAND BARTHES) - Ardiansyah Ardiansyah (Universitas Ahmad Dahlan, 2020)
This research studied the relation among green, culture, and language in Al-Qur'an because colour does not address merely about spectrum of colour. It was literature research that based on Roland Barthes's theory of connotation semiotic as this theory is part of linguistic study. The method used was Roland Barthes's semiotic elements through three stages: first was systematic stage ('alaqah ra'siyah) and syntax ('alaqah ufuqiyyah), second was signs; metaphor (majaz) and metonymy (majaz mursal), and third was stage of marking level; context and relation between denotation meaning and connotation meaning. Green in Al-Qur'an consists of four themes: (1) Plants, (2) green wood, (3) prophet Yusuf, and (4) the depiction of paradise.